2016
DOI: 10.1002/2015jd024157
|View full text |Cite
|
Sign up to set email alerts
|

Combining GOSAT XCO2 observations over land and ocean to improve regional CO2 flux estimates

Abstract: We used the GEOS‐Chem data assimilation system to examine the impact of combining Greenhouse Gases Observing Satellite (GOSAT) XCO2 data over land and ocean on regional CO2 flux estimates for 2010–2012. We found that compared to assimilating only land data, combining land and ocean data produced an a posteriori CO2 distribution that is in better agreement with independent data and fluxes that are in closer agreement with existing top‐down and bottom‐up estimates. Adding XCO2 data over oceans changed the tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 103 publications
(148 reference statements)
2
56
2
Order By: Relevance
“…They, however, used the SRON-KIT RemoTeC GOSAT retrieval with a known issue over the ocean, and concluded that adding global land and ocean observation bias correction terms to their inversion was needed to make the land-ocean flux split more realistic and to improve the seasonal cycle of CO 2 in the southern extratropics. In contrast, studies have found no noticeable bias in the ACOS B3.5 ocean glint XCO 2 retrievals relative to TCCON and a mean bias of only −0.06 ppm relative to HIPPO ; the B3.4 version we use is on average ∼ 0.2 ppm lower than B3.5 in 2010 (Deng et al, 2016). So although a small overall negative bias in the biascorrected ACOS B3.4 ocean data cannot be ruled out (and there could of course be larger negative biases on a regional scale, such as in the southern extratropics), we conclude that the land-ocean flux split in inversions using either in situ or GOSAT data is strongly influenced by error correlations and dependent on the prior uncertainties assumed.…”
Section: Flux Error Correlations and Land-ocean Partitioningcontrasting
confidence: 65%
See 2 more Smart Citations
“…They, however, used the SRON-KIT RemoTeC GOSAT retrieval with a known issue over the ocean, and concluded that adding global land and ocean observation bias correction terms to their inversion was needed to make the land-ocean flux split more realistic and to improve the seasonal cycle of CO 2 in the southern extratropics. In contrast, studies have found no noticeable bias in the ACOS B3.5 ocean glint XCO 2 retrievals relative to TCCON and a mean bias of only −0.06 ppm relative to HIPPO ; the B3.4 version we use is on average ∼ 0.2 ppm lower than B3.5 in 2010 (Deng et al, 2016). So although a small overall negative bias in the biascorrected ACOS B3.4 ocean data cannot be ruled out (and there could of course be larger negative biases on a regional scale, such as in the southern extratropics), we conclude that the land-ocean flux split in inversions using either in situ or GOSAT data is strongly influenced by error correlations and dependent on the prior uncertainties assumed.…”
Section: Flux Error Correlations and Land-ocean Partitioningcontrasting
confidence: 65%
“…For constraining fluxes at relatively high temporal resolution, observations are chosen that consist of discrete wholeair samples collected in glass flasks approximately weekly and continuous in situ tall tower measurements of CO 2 mole fraction from the NOAA ESRL Carbon Cycle Cooperative Global Air Sampling Network (Dlugokencky et al, 2013;Andrews et al, 2009) Tsutsumi et al, 2006). Both data sets are calibrated to the WMO-X2007 scale.…”
Section: Observations and Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There will always be an unsatisfactory length of analyses available for a TEM spin-up period whenever an operational weather forecast system is involved. Moreover, greenhouse gas assimilation systems are constrained (by time, computational expense, and the observing system) and thus often focus on a few years of study at one time (e.g., Deng et al, 2014Deng et al, , 2016. Thus, the challenge is to merge this small dataset into the spin-up procedure used for the TEM.…”
Section: Gem-mach-ghgmentioning
confidence: 99%
“…In the 4D-Var system, the adjoint of the GEOS-Chem model is used to optimize the fluxes. Details of the GEOS-Chem adjoint model are given in Henze et al (2007) and a description of its application for inverse modeling of atmospheric CO 2 is provided in Deng et al (2014Deng et al ( , 2016.…”
Section: Geos-chemmentioning
confidence: 99%